STRUKTUR KOMUNITAS MEIOFAUNA DI KAWASAN MANGROVE DESA TELUK UMA KABUPATEN KARIM - Suryani '; Radith Mahatma; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Information on meiofauna community structure in Indonesian mangrove areas is stilllimited compared to its vast areas. This study aimed to assess the community structureand abundance of meiofauna on four stations in mangrove areas, located in Teluk UmaVillage, Karimun Regency. Samples were collected from four stations. Station 1, 2,and 3 are dominated by mangrove vegetation Rhizophora sp., Avicennia sp., Bruguierasp., consecutively while station 4 is located in an area without mangrove vegetation(Coral Sand). Meiofauna abundance was analyzed using one-way ANOVA and Fisher'stest. The result indicated that meiofauna which were found at the study site consisted of12 taxa namely, Nematodes, Copepods, Polychaeta, Turbellarian, Cumacea,Oligochaeta, Holothuroidea, Syncarida, Isopoda, Ostracoda, Cnidaria, and Tardigrada.The average abundance of meiofauna was 3.22 ind/10 cm 2 . It was also found thatNematodes was the most abundance taxa followed by Copepoda and Polychaeta at allstations. One-way ANOVA results revealed that the abundance of meiofauna in eachstation was significantly different (F=3.52 P<0.05).